Pain mechanisma in causalgia. - Sunderland, S (1976)
A study of the clinical features of causalgia and the central neuronal effects of injuries to peripheral nerves suggests that causalgia is the functional expression of the intensity of the retrograde neuronal reaction in which pools of dorsal horn neurones become converted into foci of abnormal activity. These foci initiate a chain reaction along transmission pathways as far centrally as the cortex, causalgia being the terminal effect of this disorderly activity on the sensorium. This is the basis of the 'turbulance hypothesis' introduced to account for the pain.